- #1

- 1

- 0

√x2 + 1 + √x2 – 2x + 3 = 3

│ x-4 │ - │ 2–0,5x│ ≤ 3

│5- x2-6 │= x2-5x-6

x2-2x+3 : x2-4x+3 > -2

│ x-4 │ - │ 2–0,5x│ ≤ 3

│5- x2-6 │= x2-5x-6

x2-2x+3 : x2-4x+3 > -2

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter freakofsome
- Start date

- #1

- 1

- 0

√x2 + 1 + √x2 – 2x + 3 = 3

│ x-4 │ - │ 2–0,5x│ ≤ 3

│5- x2-6 │= x2-5x-6

x2-2x+3 : x2-4x+3 > -2

│ x-4 │ - │ 2–0,5x│ ≤ 3

│5- x2-6 │= x2-5x-6

x2-2x+3 : x2-4x+3 > -2

- #2

Mark44

Mentor

- 35,988

- 7,922

Second, you have several expressions written as x2. Is this supposed to be x

Share: